Analysis of Prevalence and Risk Factors of Adult Self-Reported Allergic Rhinitis and Asthma in Plain Lands and Hilly Areas of Shenmu City, China - Gao, Huiping; Niu, Yongliang; Wang, Qiang; Shan, Guangliang; Ma, Chao; Wang, Haiying; Hu, Yaoda; Guan, Kai; Gu, Jianqing; Wang, Jing; Wang, Tao; Zhao, Hongmei; et al. (Frontiers in Public Health, 2022)
Objective: The main aim of this study was to investigate the prevalence and risk factors of adult self-reported allergic rhinitis and asthma in plain lands and hilly areas of Shenmu City in China, and analyze the differences between regions. Methods: The multi-stage stratified random sampling was applied in a cross-sectional survey of adult residents in Shenmu City, from September to December 2019. The unconditional logistic regression analysis was used to screen the influence factors of allergic rhinitis and asthma. Results: 4,706 adults participated in the survey, and 99% (4,655 in 4,706) completed the questionnaires. The prevalence of allergic rhinitis was 25.4%, and the prevalence of asthma was 9.4%. The prevalence of the allergic rhinitis without asthma, asthma without allergic rhinitis, and the combined allergic rhinitis with asthma were 18.9%, 2.9%, and 6.5%, respectively. The prevalence of allergic rhinitis and asthma existed regional differences. The prevalence of adult self-reported allergic rhinitis was 41.5% in plain lands areas and 22.1% in hilly areas. The prevalence of adult self-reported asthma was 12.8% in plain lands and 8.8% in hilly areas. The prevalence of allergic rhinitis and asthma existed seasonal differences, with the highest prevalence from July to September. The analysis of risk factors showed that higher education, comorbidities of other allergic diseases, family history of allergies, urban, and desert areas were the risk factors for the allergic rhinitis without asthma. Aging, smoking, comorbidities of other allergic disorders, and family history of allergies were the risk factors for the asthma without allergic rhinitis. The younger age, higher education, smoking, comorbidities of other allergic diseases, family history of allergies, urban, and desert areas were the risk factors for the combined allergic rhinitis with asthma. Conclusions:The prevalence of allergic rhinitis and asthma in Shenmu City was relatively high, with regional differences. Genetic and environmental factors were the important risk factors associated with allergic rhinitis and asthma Our research would provide data support for preventing and controlling allergic rhinitis and asthma in this region in the future, and appropriate prevention and control programs should be formulated according to the characteristics of different regions.